System of evaluation of journals in Brazil: impacts of the evolution of the Qualis-periódicos criteria in the Area of Education - Sene, Laís Zaccaro; Bizelli, José Luís (Práxis Educacional, 2022)
The present article analyzes the production of the Qualis-Periódicos in Education, in the period from 2010 to 2018 - triennium 2010 to 2012; quadrennium 2013 to 2016 and mid-term evaluation on the years 2017 and 2018. The instrument serves to evaluate the production of faculty members of the Graduate System in Brazil, although it is often used for other purposes. It is possible to determine two types of change in the evaluation criteria: either incremental, between the triennium and the quadrennium; or disruptive, wherein in 2019, in the mid-term evaluation, a new factor is introduced to measure impact or citation. The research analyses are based on documental sources: the Qualis itself and the guiding and evaluative documents of the education area. The data show a considerable increase in the stratification of the journals caused by the objectification of the criteria in the first periods and a rupture in the last one; a drastic decrease of the evaluation universe with the introduction of the concept of parent area; and an uncertainty about the evaluation that will come in 2021.